The Influence of Using Coffee Plants as a Learning Medium on the Fine Motor Development of Children at Sumberjaya State Kindergarten - Sumiati, Cucum; Yudha, Rivo Panji (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
This study aims to gather data on the effect of utilizing coffee plants as a learning medium on the fine motor skills of children at TK Negeri Sumberjaya. The research employed is experimental (pre-experimental). The sample consisted of 30 students from TK Negeri Sumberjaya, serving as the experimental group. Data collection in this study was carried out using child observation sheets totaling 15 items, the data analysis method used is descriptive, with hypothesis testing conducted using the Paired Sample T-Test. Based on the results of the Paired Sample T-Test calculation, the Pre-Test and Post-Test values were found. The average Pre-Test value for children's fine motor skills, or the Mean, is 27.03. For the Post-Test, the average value of children's fine motor skills is 51.23. Since the average Pre-Test score of 27.03 is lower than the Post-Test score of 51.23, it indicates that, descriptively, there is a significant difference in children's fine motor skills between the Pre-Test and Post-Test results. With a Sig. (2-tailed) value of 0.000 0.05, H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant difference in children's fine motor skills between the Pre-Test and Post-Test, meaning that the use of coffee plant media has a positive effect on improving children's fine motor skills at Sumberjaya State Kindergarten.